Conversion of Adjustable Gastric Banding to Roux-en-Y Gastric Bypass in One or Two Steps: What Is the Best Approach? Analysis of a Multicenter Database Concerning 832 Patients - Pujol-Rafols, J (2020)
Background: Roux-en-Y gastric bypass (RYGB) is often the preferred conversion procedure for laparoscopic adjustable gastric banding (LAGB) poor responders. However, there is controversy whether it is better to convert in one or two stages. This study aims to compare the outcomes of one and two-stage conversions of LAGB to RYGB. Methods: Retrospective review of a multicenter prospectively collected database. Data on conversion in one and two stages was compared. Results: Eight hundred thirty-two patients underwent LAGB conversion to RYGB in seven specialized bariatric centers. Six hundred seventy-three (81%) were converted in one-stage. Patients in the two-stage group were more likely to have experienced technical complications, such as slippage or erosions (86% vs. 37%, p = 0.0001) and to have had a higher body mass index (BMI) (41.6 vs. 39.9 Kg/m2, p = 0.005). There were no differences in postoperative complications and mortality rates between the one-stage and two-stage groups (13.5% vs. 10.8%, and 0.7% vs. 0.0% respectively, p = ns). Mean final BMI and %total weight loss (%TWL) for the one-stage and the two-stage groups were 31.6 vs. 32.4 Kg/m2 (p = ns) and 30.4 vs. 26.8 (p = 0.017) after a mean follow-up of 33 months. Follow-up at 1, 3, and 5 years was 98%, 75%, and 54%, respectively. Conclusions: One-stage conversion of LAGB to RYGB is safe and effective. Two-stage conversion carries low morbidity and mortality in the case of band slippage, erosion, or higher BMI patients. These findings suggest the importance of patient selection when choosing the appropriate conversion approach